PENERAPAN METODE TEAM TEACHING (STUDI DESKRIPTIF DI SD AL-MA’SOEM) - Hana Nurur Rohmah (Dirasah: Jurnal Pemikiran dan Pendidikan Dasar Islam, 2023)
This research was conducted with the aim of knowing the application of the team teaching method carried out at Al-Ma'soem Elementary School. This study uses a qualitative descriptive method through data collection techniques in the form of observations and interviews. Based on the results of the research, the stages of implementing the team teaching method in learning are as follows: 1) Planning Stage, where class teachers, subject teachers and subject teachers conduct MGMP to design lesson plans. 2) Implementation Phase, namely the process of learning activities that begins with opening activities by the teacher in charge of teaching. In the core activities, teachers work together to apply the team teaching method by dividing the tasks of one teacher as a teacher and one other teacher as a companion. 3) Evaluation Phase, namely the evaluation process for teachers and students. Teacher evaluation is carried out by providing criticism and suggestions to each teacher in the team regarding the teaching process. Evaluation of students is carried out through summative and formative tests made by each teacher according to the material being taught. So that learning using the team teaching method is also very influential on the achievement of learning objectives.